Saikosaponin D Inhibits Peritoneal Fibrosis in Rats With Renal Failure by Regulation of TGFβ1/ BMP7 / Gremlin1/ Smad Pathway - Ruiqi, Liu; Ming, Pei; Qihang, Su; Yangyang, Lei; Junli, Chen; Wei, Lin; Chao, Gao; Xinyue, Liu; Kang, Yang; Hongtao, Yang (Frontiers in Pharmacology, 2021)
Peritoneal dialysis (PD) can improve the quality of life of patients with kidney disease and prolong survival. However, peritoneal fibrosis can often occur and lead to PD withdrawal. Therefore, it is imperative to better understand how to inhibit and slow down progression of peritoneal fibrosis. This study aimed to investigate the regulatory effect of Saikosaponin d (SSD), a monomer extracted from the plant Bupleurum, on peritoneal fibrosis and the contribution of TGFβ1/BMP7/Gremlin1 pathway cross-talk in this process. To this aim, we used a model 5/6 nephrectomy and peritoneal fibrosis in rats. Rats were divided into four groups, namely a control group (saline administration); a model group (dialysate administration; group M); a SSD group (dialysate and SSD administration); and a positive drug group (dialysate and Benazepril Hydrochloride administration; group M + A). Histological analysis indicated that peritoneal fibrosis occurred in all groups. WB, ELISA, and PCR essays suggested that TGFβ1 and Gremlin1 levels in group M were significantly higher than those in group C, whereas BMP7 expression was significantly lower. TGFβ1, Gremlin1 and BMP7 levels were significantly lower in the group where SSD was administered than in the other groups. The expression of BMP7 in SSD group was significantly increased. In addition, levels of Smad1/5/8 as assessed by PCR, and levels of p-Smad1/5/8 expression as assessed by WB were also significantly higher in the SSD group than in the M group. Expression of vimentin and α-SMA, two important markers of fibrosis, was also significantly decreased. Our study suggests a role for the TGFβ1/BMP7/Gremlin1/Smad pathway in peritoneal fibrosis with potential therapeutic implications. Finally, our results also suggest that the monomer SSD may be able to reverse peritoneal fibrosis via regulation of the TGFβ1/BMP7/Gremlin1/Smad pathway.